OPTIMASI SUHU KALSINASI KARBON AEROGEL BERBASIS CANGKANG KELAPA SAWIT UNTUK KATODA PADA APLIKASI BATERAI ION LITHIUM - ginting, delovita; syahputra, romi; Dahayu, Putri (Prodi Fisika FST UNJA, 2025)
Palm kernel shell (PKS)-based carbon aerogel holds potential as a cathode material in lithium-ion batteries due to its porous structure and high conductivity. This study aims to determine the optimal calcination temperature to enhance the physical and thermal properties of PKS-based carbon aerogel. Calcination was performed at 400°C for 3 hours and 450°C for 2 hours to analyze the effects on morphology, thermal stability, and density of the carbon aerogel. Scanning Electron Microscope (SEM) analysis revealed that calcination at 450°C produced a more porous and irregular structure, which supports optimal ion movement. Differential Scanning Calorimetry (DSC) testing showed higher thermal stability at 450°C, with a total energy of -74.54 J/g. Additionally, the density of carbon aerogel at 450°C was 0.75 g/cm³, lower than 0.83 g/cm³ at 400°C, indicating better porosity for ionic conductivity. Therefore, a calcination temperature of 450°C for 2 hours is recommended as the optimal condition to improve carbon aerogel performance for lithium-ion battery cathode applications.